2013
DOI: 10.4103/0974-7753.125618
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris with loss of hair on the scalp

Abstract: Pemphigus vulgaris is an autoimmune disease, which leads to flaccid bullae and erosions. Although the scalp is commonly involved, hair loss is rarely seen. We herein report a case of 32-year-old female patient with a 2-year history of pemphigus vulgaris, involving the skin and mucosa. Although clinical improvement was achieved with oral corticosteroids and mycophenolate mofetil, the patient developed tender plaques on her scalp, accompanied by hair loss. Histopathology and direct immunofluorescence were consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Scalp lesions in pemphigus may lead to alopecia. Nonscarring alopecia was reported to be an unusual manifestation of scalp pemphigus [ 24 ]. Veraitch et al described 5 patients with pemphigus vulgaris and progressive hair loss with alopecic patches [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scalp lesions in pemphigus may lead to alopecia. Nonscarring alopecia was reported to be an unusual manifestation of scalp pemphigus [ 24 ]. Veraitch et al described 5 patients with pemphigus vulgaris and progressive hair loss with alopecic patches [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested that the combination of anti-desmoglein autoantibody-mediated acantholysis with a concomitant infection may cause the weakening of the hair follicle anchorage and result in alopecia [ 5 ]. Hadayer et al reported a case of a patient with pemphigus vulgaris, in whom alopecia was also accompanied by Staphylococcus aureus infection [ 24 ]. Our literature search revealed only one case report of nonscarring alopecia occurring in pemphigus foliaceus [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 , 5 Frequently, the scalp is the first site of clinical manifestation of the disease. 4 , 6 Isolated pemphigus lesions of the scalp have been reported in the literature. 7 - 9 Occasionally, scalp lesions may be extremely resistant to treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Scalp lesions in the course of pemphigus can lead to several types of non-cicatricial and cicatricial alopecia. 6 , 12 - 14 Thus, differential diagnosis of isolated scalp lesions and hair loss in the course of pemphigus…”
Section: Introductionmentioning
confidence: 99%